The Influence of Le Corbusier On the emergence of the Aesthetic Values in the Modern Architecture of Cyprus - Farhan Abdullah Ali (Alanya Hamdullah Emin Paşa Üniversitesi, 2018)
Modernity has significantly influenced the branches of human knowledge; architecture has a substantial share in this effect. Modern architecture, in turn, was not a negative recipient to impact, but it was a positive catalyst for decades. Moreover, it did not limit to certain geographic boundaries, but it has spread all over the world and Cyprus was not an exception. Due to most of the Cypriot pioneer architects were studied in Europe; Cyprus was the incubator that has many architectural distinctive pieces of evidence of modern architecture. Perhaps the expert reader of the modern architectural discourse of Cyprus could distinguish numerous aesthetic features in Cyprus Buildings especially the private residences and their appearance is credited back to one of the pioneers of modern architecture; Le Corbusier. The research paper is an attempt to determine the influence of the principles that Le Corbusier claimed as keystones of modern architecture in early twenty century and how impressed on the emergence of aesthetic values of the modern architecture of Cyprus as well. The paper takes two works of Neoptolemos Michaelides, as a case study (Neoptolemos Michaelides is considered the father of Cyprus modern architecture). The first case study is his and wife private residence, which considers the icon of the modern residential architecture of Cyprus and the other is the first residential project designed by him Theotodos Kanthos residence.